فعالية الإرشاد النفسي البنائي في تخفيف أزمة الهوية لدى طالبات جامعة القصيم: دراسة وصفية شبه تجريبية - مرسي، منى مصطفي فرغلي (جامعة الأزهر - كلية التربية, 2019)
تهدف الدراسة الحالية إلى إلقاء المزيد من البحث حول ملامح أزمة الهوية في البيئة السعودية ومستوى انتشارها بين طلاب وطالبات الجامعة بجامعة القصيم، والكشف عن طبيعة الفروق بين الذكور والإناث في درجة أزمة الهوية، وكذلك إلقاء الضوء على طبيعة الإرشاد النفسي البنائي، ومفهوم البنائية، ذلك المفهوم الثري والمتعدد المعاني والأبعاد والوصول إلى مكوناته الرئيسية، ومحاولة الفهم المتعمق لطبيعته، باعتبار العملية البنائية ذات طبيعة دينامية تنموية للواقع والخبرات الإنسانية. والقيام بإعداد البرنامج الذي يعتمد على إعادة صياغة البناء الذاتي للأفراد. والتعرف على فعاليته في التخفيف من أزمة الهوية لدى عينة من الطالبات بجامعة القصيم، وكذلك التعرف على مدى استمرارية أثر البرنامج بعد انتهاء تطبيق البرنامج وأثناء فترة المتابعة. ولتحقيق هذه الأهداف استخدمت الباحثة المنهج الوصفي الذي يعي بالناحية التشخيصية لمتغير الدراسة المتمثل في أزمة الهوية، والمنهج شبه التجريبي والذي يعد أكثر المناهج ملائمة لتحقيق هدف الدراسة. واستخدمت الباحثة الأدوات الأتية: استمارة تقدير الوضع الاجتماعي الثقافي الاقتصادي للبيئة السعودية (إعداد الشربيني، أبو السعود ٢٠١٣) مقياس أزمة الهوية، برنامج الإرشاد النفسي البنائي (إعداد الباحثة). وذلك على عينة أساسية من طلاب وطالبات جامعة القصيم، انقسمت العينة الأساسية إلى عينتين فرعيتين: العينة التي تتصل بالجانب التشخيصي السيكومتري وبلغ عددها (30) طالب وطالبة بجامعة القصيم، والعينة التجريبية وبلغ عددها (٤٠) طالبة من طالبات الجامعة، والتي جرى تقسيمها إلى مجموعتين: مجموعة تجريبية خضعت لبرنامج الإرشاد النفسي البنائي وعددها (20) طالبة، ومجموعة ضابطة وعددها (٢٠) طالبة. وقد توصلت الدراسة إلى النتائج الآتية: توجد فروق ذات دلالة إحصائية بين متوسطات أبعاد مقياس أزمة الهوية وكذلك الدرجة الكلية وبين المتوسطات الفرضية لهذه الأبعاد والدرجة الكلية لصالح متوسطات العينة. لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات الطلاب والطالبات على أبعاد مقياس أزمة الهوية والدرجة الكلية لها. توجد فروق ذات دلالة إحصائية بين متوسطات درجات طالبات المجموعتين التجريبية والضابطة في القياس البعدي على أبعاد مقياس أزمة الهوية والدرجة الكلية له في اتجاه المجموعة التجريبية. توجد فروق ذات دلالة إحصائية بين متوسطات درجات طالبات المجموعة التجريبية في القياس القبلي والبعدي على أبعاد مقياس أزمة الهوية والدرجة الكلية له في اتجاه القياس البعدي. توجد فروق ذات دلالة إحصائية بين متوسطات درجات طالبات المجموعة التجريبية في القياس البعدي والتتبعي على أبعاد مقياس أزمة الهوية والدرجة الكلية له في اتجاه القياس التتبعي
The present study aims to shed more research on the features of identity crisis in the Saudi environment and the level of its spread among university students in Qassim University, and to reveal the nature of the differences between males and females in the degree of identity crisis, as well as shed light on the nature of psychological counseling constructivist, and the concept of constructivism, that concept The rich and multi-dimensional and access to its main components, and an attempt to understand the depth of its nature, considering the construction process of a dynamic developmental nature of reality and human experiences. Constructing a structured treatment program that relies on individual self-reconstruction. And to identify its effectiveness in alleviating the identity crisis among a sample of students at the University of Qassim, as well as to identify the continuity of the impact of the program after the completion of the program and during the follow-up period. To achieve these goals, the researcher used the descriptive approach, which means diagnostic aspects of the study variable, namely the identity crisis, and the quasi-experimental approach, which is the most appropriate approach to achieve the study goal. The researcher used the following tools: Assessment form socio-economic status of the Saudi environment (prepared by Sherbini, Abu Saud 2013) Identity Crisis Scale, the program of psychological counseling construction (researcher). On the basic sample of the students of Qassim University, the basic sample was divided into two sub-samples: the sample that relates to the psychometric diagnostic side and the number of (300) male and female students in the Qaseem University, and the experimental sample of (40) female university students, which was divided into two groups: Experimental group underwent a program of psychological counseling construction (20) students, and a control group of (20) students. The study reached the following results: • There are statistically significant differences between the mean dimensions of the identity crisis scale as well as the total score and between the hypothesis averages of these dimensions and the total score in favor of the sample mean. • There are no statistically significant differences between the average scores of male and female students on the dimensions of the identity crisis scale and the total score. • There are statistically significant differences between the mean scores of the experimental and control groups students in the telemetry on the dimensions of the identity crisis scale and its total score in the direction of the experimental group. • There are statistically significant differences between the mean scores of the experimental group students in the pre and post measurement on the dimensions of the identity crisis scale and its total score in the direction of the post measurement. • There are statistically significant differences between the mean scores of the experimental group students in the telemetry and tracking on the dimensions of the identity crisis scale and its total score in the direction of the tracking measurement.
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- الإرشاد النفسي -- الهوية الوطنية -- أزمة الهوية -- التعليم الجامعي -- طلاب الجامعات -- جامعة القصيم -- الدراسات الوصفية